1999
DOI: 10.1128/iai.67.1.337-341.1999
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriInfection in Immunized Mice Lacking Major Histocompatibility Complex Class I and Class II Functions

Abstract: The role of major histocompatibility complex (MHC) class I- and class II-restricted functions in Helicobacter pyloriinfection and immunity upon oral immunization was examined in vivo. Experimental challenge with H. pylori SS1 resulted in significantly greater (P ≤ 0.025) colonization of MHC class I and class II mutant mice than C57BL/6 wild-type mice. Oral immunization with H. pylori whole-cell lysates and cholera toxin adjuvant significantly reduced the magnitude of H. pylori infection in C57BL/6 wild-type (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(43 citation statements)
references
References 30 publications
1
41
0
1
Order By: Relevance
“…The immune responses to H. pylori that occur in experimentally infected animals and in naturally infected humans are typically ineffective in eradicating H. pylori. However, studies in animal models indicate that H. pylori infection can be prevented by prophylactic immunization (Ermak et al, 1998;Pappo et al, 1999;Akhiani et al, 2002Akhiani et al, , 2004Garhart et al, 2003), and established infections can potentially be eradicated via therapeutic immunization (Vyas & Sihorkar, 1999;Sutton et al, 2000;Li et al, 2004). An important goal for future studies will be to understand more clearly the immunologic determinants of protective immunity against H. pylori, and to determine why immune responses to H. pylori fail to eradicate the infection in most infected humans.…”
Section: Discussionmentioning
confidence: 99%
“…The immune responses to H. pylori that occur in experimentally infected animals and in naturally infected humans are typically ineffective in eradicating H. pylori. However, studies in animal models indicate that H. pylori infection can be prevented by prophylactic immunization (Ermak et al, 1998;Pappo et al, 1999;Akhiani et al, 2002Akhiani et al, , 2004Garhart et al, 2003), and established infections can potentially be eradicated via therapeutic immunization (Vyas & Sihorkar, 1999;Sutton et al, 2000;Li et al, 2004). An important goal for future studies will be to understand more clearly the immunologic determinants of protective immunity against H. pylori, and to determine why immune responses to H. pylori fail to eradicate the infection in most infected humans.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have attempted to reveal the immunological basis of immunization. As a result of studies using knockout mice, it is now clear that protection is MHCII-dependant (3,4) but that antibodies IFN-γ (5) and IL-4 and IL-13 (6) are not required. Furthermore, it has been reported that CD4+ T cell lines of Th2 (7) or mixed-type (8) could confer protection after transfer to naïve recipients.…”
mentioning
confidence: 99%
“…Vaccine-induced protection against Helicobacter infection in mouse models can occur independently of antibodies (Ermak et al, 1998;Blanchard et al, 1999;Sutton et al, 2000), but has an absolute requirement for CD4 1 T helper cells (Ermak et al, 1998;Pappo et al, 1999). This suggests that the ineffectiveness of prophylactic immunization in naïve C57BL/6 mice may be due to either a poor CD4 response to the rHpaA protein, or a poor translation in immunity from the recombinant vaccine antigen to the native form expressed by the bacteria.…”
Section: Discussionmentioning
confidence: 99%